TRUEBLE: da ferramenta educacional ao AVA por meio de reestruturação funcional e pedagógica - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This work presents the reengineering of the TRUEBLE educational app for teaching propositional logic, motivated by prior evaluations that revealed usability and pedagogical mediation issues. The goal was to transform it into a Virtual Learning Environment through heuristic evaluation and requirements reengineering. High-fidelity prototypes were produced, and an A/B test showed preference and higher satisfaction with the redesigned version.
Keywords: Ciência da computação; Ambiente Virtual de Aprendizagem (AVA); Reengenharia de software; Aplicativo educacional; Computer science; Virtual Learning Environment; Software reengineering; Educational application; CIENCIAS EXATAS E DA TERRA